The integration of the District health system in South Africa. Negotiating the boundaries between researcher and facilitator - Parr, Jennifer (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
The integration of the District health system in South Africa. Negotiating the boundaries between researcher and facilitator